Pengaruh temperatur elektrolit terhadap ketebalan dan kuat lekat baja karbon rendah pada proses elektroplating - Asroni Asroni; Eko Budiyanto; Tri Cahyo Wahyudi; I Wayan Suarca (TURBO [Tulisan Riset Berbasis Online], 2021)
The development of industry as well as science and technology requires humans to fulfill various kinds of needs in their lives. One of them is the need for metal-based goods. Many objects around us, both in the automotive industry and in the steel-based industry for household purposes, etc., are given a metallic finish to protect and beautify the metal. The metal coating technique that is often used in the metal industry is electroplating. Electroplating comes from two words, namely electro and plating or electricity and coating that uses a deposition system. The purpose of this study was to determine the effect of electrolyte temperature on the thickness and adhesive strength of low carbon steel in the electroplating process. The cathode used is low carbon steel with dimensions of 70 mm x 25 mm x 20 mm, while the anode used is Nickel (Ni) and the bath for plating is 60 cm long, 30 cm depth, and 30 cm wide. Two anodes on the right and left side of the anode with an anode-cathode distance of 10 cm, and using an electric voltage of 7.5 Volts, and using variations in electrolyte temperature of 450C, 500C, 550C, 600C, 650C and room temperature. From the results of the study found the optimal thickness value with 0.021 mm at a temperature of 600C. Meanwhile, the optimal value for coating adhesive strength from electroplating research is 60â„ƒ with a very high adhesive strength value of 26.53 MPa.